Edukasi dan Pendampingan Evidence-Based Practice untuk Mendukung Asuhan Keperawatan Berkualitas - Noyumala; Rezqiqah Aulia Rahmat (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2026)
Abstract Evidence-Based Practice (EBP) is an approach to nursing care that integrates the best scientific evidence, clinical expertise, and patient values ​​to improve the quality of nursing care. However, the implementation of EBP in the field still faces various obstacles, particularly nurses' limited knowledge and skills in accessing and applying scientific evidence. This community service activity aims to improve nurses' knowledge and skills in implementing Evidence-Based Practice through education and mentoring. Implementation methods include counseling, interactive discussions, EBP implementation mentoring, and the distribution of brochures as supporting media. The results of the activity indicate an increase in participants' knowledge, attitudes, and abilities in understanding and applying EBP principles in nursing care. This activity is expected to support the continuous improvement of the quality of nursing care. Keywords: Community Service, Evidence-Based Practice, Nursing, Quality of Care Abstrak Evidence-Based Practice (EBP) merupakan pendekatan dalam asuhan keperawatan yang mengintegrasikan bukti ilmiah terbaik, keahlian klinis, dan nilai pasien untuk meningkatkan mutu pelayanan keperawatan. Namun, penerapan EBP di lapangan masih menghadapi berbagai kendala, terutama keterbatasan pengetahuan dan keterampilan perawat dalam mengakses serta menerapkan bukti ilmiah. Kegiatan pengabdian kepada masyarakat ini bertujuan untuk meningkatkan pengetahuan dan keterampilan perawat dalam menerapkan Evidence-Based Practice melalui kegiatan edukasi dan pendampingan. Metode pelaksanaan meliputi penyuluhan, diskusi interaktif, pendampingan penerapan EBP, serta pembagian brosur sebagai media pendukung. Hasil kegiatan menunjukkan adanya peningkatan pengetahuan, sikap, dan kemampuan peserta dalam memahami serta menerapkan prinsip EBP dalam asuhan keperawatan. Kegiatan ini diharapkan dapat mendukung peningkatan kualitas asuhan keperawatan secara berkelanjutan. Kata Kunci: Pengabdian Kepada Masyarakat, Evidence-Based Practice, Keperawatan, Mutu Asuhan